CHATBOT SEBAGAI GURU VIRTUAL UNTUK MATA KULIAH DATA MINING: CHATBOT SEBAGAI GURU VIRTUAL UNTUK MATA KULIAH DATA MINING - Sabna, Eka (Jurnal Ilmu Komputer, 2022)
Abstract A chatbot is an application (service) that interacts with users through text conversations. Chatbots work to replace the role of humans in serving conversations through messaging applications. The chatbot that is built will be virtual assisting that will help students learn at home. Chatbots can only answer questions based on patterns that have been stored in the chatbot's knowledge base. Chatbots are automated conversational agents that interact with users using natural human language that can help anytime and anywhere. This chatbot is applied as a Virtual Teacher who can provide information and learning materials to students in Data Mining courses. Keywords: C4.5, NBC, GPA, performance, student Abstrak Chatbot merupakan aplikasi (layanan) yang berinteraksi dengan pengguna melalui percakapan teks. Chatbot bekerja untuk menggantikan peranan manusia dalam melayani pembicaraan melalui aplikasi pesan. chatbot yang dibangun akan menjadi virtual assisting yang akan membantu Mahasiswa dalam belajar dirumah. Chatbot hanya dapat menjawab pertanyaan berdasarkan pola yang telah disimpan di dalam knowledge base chatbot. Chatbot adalah agen percakapan otomatis yang berinteraksi dengan pengguna menggunakan bahasa alami manusia yang dapat membantu kapan saja dan dimana saja. Chatbot ini di aplikasikan sebagai Guru Virtual yang dapat memberikan informasi dan materi pembelajaran terhadap mahasiswa dalam matakuliah Data Mining. Kata Kunci : Chatbot, Data Mining, Virtual Teacher, Student, Learning